Preparation of an N–S dual-doped black fungus porous carbon matrix and its application in high-performance Li–S batteries - Zhao, Liping; Zhao, Ye; Zhao, Lihe; Liu, Gang (Frontiers in Chemistry, 2023)
A nitrogen–sulfur dual-doped black fungus porous carbon (NS-FPC) matrix was prepared with natural black fungus as the carbon source and cysteine as the nitrogen–sulfur source. A black fungus-based solution was obtained by hydrothermal treatment. After further carbonization activation and combination with sulfur processing, the NS-FPC/S positive electrode materials were prepared. The uniform recombination of biomass carbon provides an efficient conductive framework for sulfur. The porous structure is conducive to the transport of electrolytes. Heteroatom doping can provide a more active site. The structure and composition analyses of the materials were carried out using X-ray diffraction (XRD). The electronic binding energy and bonding state were analyzed by X-ray photoelectron spectroscopy (XPS). The morphology was observed by scanning electron microscopy and transmission electron microscopy. The specific surface area and pore size distribution were analyzed using an N2 adsorption–desorption experiment. Sulfur loading was determined through thermogravimetric analysis. The electrochemical performance of NS-FPC/S in Li–S batteries was systematically investigated. The result shows that the NS-FPC/S electrode maintains more than 1,000 mAh g-1 reversible capacity after 100 cycles at 0.2 C current density, with a capacity retention of 85%. The cycle and rate performance are both considerably superior to those of traditional activated carbon materials.